Valine 738 and lysine 735 in the fifth transmembrane domain of rTas1r3 mediate insensitivity towards lactisole of the rat sweet taste receptor - Meyerhof Wolfgang; Bufe Bernd; Winnig Marcel (BMC Neuroscience, 2005)
Abstract Background The sweet taste inhibitor lactisole acts on the human sweet taste receptor heteromer TAS1R2-TAS1R3 but not on its rodent counterpart. Recently, it was shown that the lactisole sensitivity of the human sweet taste receptor involves the part of TAS1R3 encompassing the seven transmembrane regions but not the huge N-terminal domain. Using mutational analysis we investigated which amino acid residues distinguish lactisole insensitive rat from sensitive human T1R3 receptors. Results The functional analysis of specific receptor mutants in HEK293T cells revealed that the exchange of valine 738 in the fifth transmembrane domain of rTas1r3 by an alanine is sufficient to confer lactisole sensitivity to the rat sweet taste receptor. The sensitivity of this receptor mutant is ~2 fold lower than the sensitivity of the human sweet taste receptor. Additional substitution of lysine 735 by phenylalanine in rTas1r3 results in a rat sweet taste receptor that is as sensitive to lactisole as its human counterpart. The exchange of valine 738 to alanine was accompanied by a ~50% reduction in receptor efficacy. This effect was seen with all six different sweet compounds examined. Conclusion The lactisole insensitivity of rat sweet taste receptor is caused by only two amino acids in transmembrane region five, which is critical for the interaction of lactisole with the sweet taste receptor. The observation that the mutant receptor simultaneously displays a generally reduced sensitivity towards all agonists suggests that the lactisole insensitivity of the rodent receptor might be more likely caused by the inaccessibility of the lactisole binding site rather then by its direct disruption.